MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PROJECT BASED LEARNINGDI MA SHINE AL-FALAH - HELTI AFRINA A, Drs. Eswendi, M.Pd., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of the research is to improve the students’ learning outcomes at grade X 1 of MA Shine Al-Falah Padang in learning sklill through the application of learning model of Project Based Learning. The research method used is classroom action  esearch. The procedure of the researvh shaped of a cycle which consisting of three stages: planning, action/observastion, and reflection. The result showed that the  earning of project Based Learning in sklill material can improve the students’  earning outcomes above the minimum mastery criteria. This is evidenceinthe first cycle with an average value 73,5 to 82,5 in the second cycle.Keywords: Students’ Learning Outcomes, Project Based Learning,Learning Sklills